Design of Optimal High-Frequency Wave Self Mixing-VCO Architecture - L. Suneetha,Dr. G. Chenchukrishnaiah,Kiran Kumar Vaka (Cuestiones de Fisioterapia, 2025)
One essential part of wired and wireless application systems is a voltage-controlled oscillator (VCO), for frequency conversion, it produces local oscillation signals, and for mixed-mode circuits, it produces fast clock signals. Recently, new millimeter-wave frequency-based high-speed wireless technologies have been created, implementing the LO signal in a synthesizer requires the use of a voltage-controlled oscillator (VCO) where the close-in phase noise is low and the oscillation frequency is high. In the millimeter-wave range, the VCO is essential for phase-locked loop (PLL) frequency control because it achieves a balance between frequency tuning range (FTR) and phase noise (PN). Communication systems running at GHz and higher frequency bands require the development of an on-chip local oscillator (LO) with a wide tuning range and outstanding spectral purity, LO (Local Osciallator) synthesis approaches must overcome a number of design challenges. To solve the above issues, design of optimal high-frequency wave self-mixing VCO architecture is presented. In order to achieve the required performance, in the Self-Mixing VCO (SMV), the first (f0) and second (2f0) harmonics are generated by the VCO core and combined.